Differential diagnosis of Crohn’s disease using antibodies to glycoprotein 2 and Saccharomyces cerevisiae - , Ali Erkan Duman, Sadettin Hülagü, Altay Çelebi, Uğur Korkmaz, Mahmut Mert Musul, Ömer Şentürk, Göktuğ Şirin, Hasan Yılmaz, Deniz Öğütmen Koç, Gökhan Dindar; et al. (Turkish Journal of Gastroenterology 1, 2019)
Background/Aims: Glycoprotein 2 (GP2), the major autoantigen of Crohn’s disease (CD)-specific pancreatic autoantibodies, is reportedly correlated with several characteristics of CD. We investigated this serological marker in Turkish patients with CD and assessed its utility in combination with anti-Saccharomyces cerevisiae antibodies (ASCAs) for differential diagnosis of CD. Materials and Methods: A total of 60 patients with CD, 62 patients with ulcerative colitis (UC), and 46 healthy controls with a definite diagnosis who were similar in age and sex were enrolled in the study conducted from November 2011 to October 2012. ASCA and anti-GP2 levels were measured using commercially available kits. Results: Anti-GP2 IgA and IgG levels were higher in patients with CD (25%) than in those with UC (5%) and controls (2%). The seroprevalence of anti-GP2 IgA was markedly higher than that of IgG in patients with CD in contrast to previous studies. The specificity and positive predictive value of seropositivity for both ASCA and anti-GP2 were 100%. ASCA IgA seropositivity was correlated with a complicated disease course and a history of surgery. There was no correlation between anti-GP2 seropositivity and disease location, disease behavior, or a history of surgery. Conclusion: The combination of ASCA and anti-GP2 may enable differentiation of CD from UC. As ASCA seropositivity is associated with a more complicated disease course, patients seropositive for ASCA at the initial diagnosis should undergo more intense therapy. Cite this article as: Duman AE, Hülagü S, Çelebi A, et al. Differential diagnosis of Crohn’s disease using antibodies to glycoprotein 2 and Saccharomyces cerevisiae. Turk J Gastroenterol 2019; 30: 21-7.